LA INVESTIGACION COMO MEDIO DE ENSEÑANZA DE LA EPIDEMIOLOGIA - Madrid Ch., Marco (1999)
In the Denthistry School of San marcos University, the students of the fourth year made the Epidemiolog Study "Oral morbidity and treatment needs in the Comunity Jerusalem, Puente Piedra y Magdalena in Perú'' and they knew and understanded this Science, this experience the field help much to the students to integrate the theoric knowbegge.